Prospek Lulusan Prodi Pendidikan Bahasa Arab IAIN Parepare - Jannah, Raodhatul; Renaldy, Asfar (Assuthur: Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to answer the phenomena that arise among students and prospective students of the IAIN Parepare Arabic Language Education study program who experience anxiety about future job prospects. This research seeks to answer this anxiety by conducting an alumni tracking study to find out the profile of graduates and the contribution of PBA alumni in the world of work. This type of research is descriptive qualitative research which aims to explore in depth the portrait of PBA study program alumni. In this case, the information collected is: 1) alumni work, 2) suitability with graduate profiles, and 3) alumni waiting period after graduating from IAIN Parepare. This research was conducted on PBA study program alumni in 2018, totaling 25 people. The results of this study indicate that 80% or around 20 alumni are already working and the remaining 20% ​​choose not to work. Then of the 20 alumni, 75% of them work as education practitioners, and 10% work as creative economy actors. While another 15% work as educational practitioners as well as creative economy actors. So it can be concluded that PBA study program has high potential as a forum to prepare alumni for the world of work, and job opportunities for PBA alumni are very high as evidenced by the presentation of graduates who are active in the world of work.